Novel variants of SERPIN1A gene: Interplay between alpha1-antitrypsin deficiency and chronic obstructive pulmonary disease. (August 2016) - Bashir, Arif; Shah, Naveed Nazir; Hazari, Younis Mohammad; Habib, Mudasir; Bashir, Samirul; Hilal, Nazia; Banday, Mariam; Asrafuzzaman, Syed; Fazili, Khalid Majid
Abstract: Alpha1-antitrypsin (AAT) is one of the major circulating anti-protease whose levels in circulation are raised during excessive amount of proteases, especially neutrophil elastase (NE) released during the course of inflammation. Proteolytic attack of NE on peripheral organs, more exclusively on lung parenchyma has severe consequence that may precipitate pulmonary emphysema. Normally, human body has its own molecular and physiological mechanisms to synthesize and regulate the production of anti-protease like AAT to mitigate the extent of inflammatory damage. AAT coded by serine-protease inhibitor ( SERPINA1 ) is predominantly expressed in hepatocytes and to some extent by macrophages, monocytes, lung tissue etc. The observation that persons with AAT deficiency developed chronic obstructive pulmonary disease (COPD) and early-onset of emphysema proposed a role for pathways connecting AAT in pathogenesis. Extensive studies have been done till now to bridge a connection between numerous genetic polymorphisms of SERPINA1 gene and the early onset of COPD. Here in this review, we have comprehensively discussed some of the variants of SERPINA1 gene discovered till date and their association with the exacerbation of obstructive pulmonary disease. Highlights: AAT deficiency in the human serum bridges a connection between genetics and the early onset of COPD. The unregulated protease activity causes progressive lung parenchyma degradation and accelerated decline in lung function. Gain-of-toxic function of Z-AAT in hepatocytes has severe consequences ranging from cirrhosis to hepatocellular carcinoma. Z-AAT expression activates nuclear factor (NF) κB by a calcium-driven pathway that is independent of the UPR. Null or silent mutations of the SERPINA1 gene typically show complete absence of AAT in the human serum.